In vivo MRI and PET imaging in a translational ILD mouse model expressing non-resolving fibrosis and bronchiectasis-like pathology after repeated systemic exposure to bleomycin - Mahmutovic Persson, Irma; Fransén Petterson, Nina; Liu, Jian; in ‘t Zandt, René; Carvalho, Carla; Örbom, Anders; Olsson, Lars E.; von Wachenfeldt, Karin (Frontiers in Medicine, 2024)
Drug-induced ILD is crucial to detect early in order to achieve the best treatment outcome.Optimally non-invasive imaging biomarkers can be used for early detection of disease progression and treatment follow-up. Therefore, reliable in vivo models are warranted in new imaging biomarker development, to accelerate better targeted treatment options. Single-dose bleomycin models have for a long time served as a reference model in fibrosis-and lung injury research. Here we aimed to use a clinically more relevant animal model by systemic exposure to bleomycin and assessing disease progression over time by combined MRI and PET imaging.Methods: C57BL/6 mice received bleomycin, (i.p. 35iU/kg) or saline as control, twice per week, for 4 weeks. Mice were monitored until two weeks after cessation of bleomycin administration (w4+1 and w4+2), referred to as the resting period. MRI scans were performed in weeks 3 and 4, and during the resting weeks. [ 18 F]FDG-PET was performed at the last week of dosing (w4) and two weeks after last dosing (w4+2). Lung tissue sections were stained with Masson's trichrome and evaluated by modified Ashcroft scoring. Lung volume and lesion volumes were assessed by MRI, as well as 3D mapping of the central airways.Results and Discussion: Bleomycin-challenged mice showed increased lung weights (p<0.05) while total lung volume was unchanged (w4 and onwards). Histology analysis demonstrated fibrotic lesions emanating from the distal parts of the lung. Fibrosis progression was visualised by MRI with significantly increased high signal in bleomycin-exposed lungs compared to controls (p<0.05). Also, significant increase of central airway diameter (p<0.01) was displayed in bleomycin-exposed animals compared to controls, and further continued to dilate as the disease progressed, comparing the bleomycin groups over time (p<0.05-0.001). Lung [ 18 F]FDG uptake was significantly elevated in bleomycin-exposed mice compared to controls (p<0.05).Non-invasive imaging displayed progressing lesions in the lungs of bleomycinexposed mice, using two distinct MRI sequences and [ 18 F]FDG-PET. With observed fibrosis progression emanating from distal lung areas, dilation of the central airways was evident. Taken together, this chronic bleomycin-exposure model is translationally more relevant for studying lung injury in ILD and particularly in the context of DIILD.